Causes of financial instability - Dirk Bezemer (Levy Economics Institute of Bard College, 2011)
Given the economy's complex behavior and sudden transitions as evidenced in the 2007-08 crisis, agent-based models are widely considered a promising alternative to current macroeconomic practice dominated by DSGE models. Their failure is commonly interpreted as a failure to incorporate heterogeneous interacting agents. This paper explains that complex behavior and sudden transitions also arise from the economy's financial structure as reflected in its balance sheets, not just from heterogeneous interacting agents. It introduces flow-of-funds and accounting models, which were preeminent in successful anticipations of the recent crisis. In illustration, a simple balance-sheet model of the economy is developed to demonstrate that nonlinear behavior and sudden transition may arise from the economy's balance-sheet structure, even without any microfoundations. The paper concludes by discussing one recent example of combining flow-of-funds and agent-based models. This appears a promising avenue for future research.
Keywords: B52; C63; E32; E37; E44; 330; credit crisis; finance; complex systems; DSGE; agent-based models; stockflow consistent models